T-differentiable functionals and ther critical points - Mel'nik, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The critical points of the functionals F: D X → R defined on "nonlinear" sets D in the topological vector spaces X are studied. A construction of a T-derivative is suggested for these functionals and compared with to known constructions. The concept of a weak critical point is introduced and Coleman’s principle is justified for T-differentiable functionals.